2020
DOI: 10.1108/jima-09-2019-0186
|View full text |Cite
|
Sign up to set email alerts
|

A conceptualization of the role of religiosity in online collaborative consumption behavior

Abstract: Purpose The purpose of this paper is to explore the role of religiosity in online collaborative consumption contexts. It analyzes the impact of religiosity in influencing consumer life decisions and behaviors. The proposed framework is based on the norm activation theory (NAT) with religiosity added to it based on the extant literature. The paper aims to provide implications for marketing researchers and practitioners derived from its analysis and propositions. Design/methodology/approach The current paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 91 publications
(119 reference statements)
0
14
0
1
Order By: Relevance
“…The sense of trust and fairness about service providers and their service policy helps customers enjoy a service. More specifically, when customers are confident in service quality, service environment, and service delivery, customers' perceptions of perceived usefulness increase (Abutaleb et al, 2020). Therefore, in the context of CC, it can be assumed that customers' perceptions of trust affect their sense of perceived usefulness.…”
Section: Justification For the Modelmentioning
confidence: 99%
“…The sense of trust and fairness about service providers and their service policy helps customers enjoy a service. More specifically, when customers are confident in service quality, service environment, and service delivery, customers' perceptions of perceived usefulness increase (Abutaleb et al, 2020). Therefore, in the context of CC, it can be assumed that customers' perceptions of trust affect their sense of perceived usefulness.…”
Section: Justification For the Modelmentioning
confidence: 99%
“…Hence, it is claimed that it is important to integrate rational choice theories and pro-socially motivated ones. Another study was conducted by Abutaleb et al (2020Abutaleb et al ( , 2021 to examine the impact of personal norms when added to the TPB. Results showed that personal norms along with other TPB variable helped in explaining variance in millennials' intentions towards collaborative consumption practices.…”
Section: Norm Activation Theorymentioning
confidence: 99%
“…Several previous studies have documented the impact of beliefs on personal norms (Abutaleb et al , 2020; Shin et al , 2018; Liu et al , 2020). However, fewer studies have examined the mediation effect of norms between beliefs and behavioral intention (Dalvi-Esfahani et al , 2017; Vaske et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%